Prehospital Noninvasive Ventilation: An NAEMSP Position Statement and Resource Document. (4th January 2022) - McCoy, Andrew M.; Morris, Dylan; Tanaka, Kaori; Wright, Angela; Guyette, Francis X.; Martin-Gill, Christian
Abstract: Noninvasive ventilation (NIV), including bilevel positive airway pressure and continuous positive airway pressure, is a safe and important therapeutic option in the management of prehospital respiratory distress. NAEMSP recommends: NIV should be used in the management of prehospital patients with respiratory failure, such as those with chronic obstructive pulmonary disease, asthma, and pulmonary edema. NIV is a safe intervention for use by Emergency Medical Technicians. Medical directors must assure adequate training in NIV, including appropriate patient selection, NIV system operation, administration of adjunctive medications, and assessment of clinical response. Medical directors must implement quality assessment and improvement programs to assure optimal application of and outcomes from NIV. Novel NIV methods such as high-flow nasal cannula and helmet ventilation may have a role in prehospital care.